Hard Carbon: Quinone‐Based Redox Supercapacitor Using Highly Conductive Hard Carbon Derived from Oak Wood (Adv. Sustainable Syst. 11/2019). (14th November 2019) - Katsuyama, Yuto; Nakayasu, Yuta; Oizumi, Kotaro; Fujihara, Yui; Kobayashi, Hiroaki; Honma, Itaru
Abstract : In article number 1900083, Yuta Nakayasu and co‐workers, prepare hard carbon by Japanese traditional carbonization of oak wood, showing a conductivity as high as that of artificial graphite. The use of oak‐derived hard carbon for quinone‐based organic supercapacitors dramatically improves the utilization rate of anode active material (97.6%) while that in conventional reports using petroleum‐derived activated carbon is 80% at most.